Optimisation of aero and industrial gas turbine design for the environment - Jackson, Anthony J. B. (Cranfield University, 2009)
The aspects of gas turbine design that are explored herein are focussed on reduction or elimination of carbon dioxide (CO2) emissions and reduction of noise. There are 3 separate but related investigations. 1. Aero gas turbine engine thermodynamic cycles for subsonic transport aircraft are explored to optimise performance (thus reducing CO2 emissions) and to minimise noise; particular attention is paid to choices of fan pressure ratio, bypass ratio, installation configuration and fan design. Turbofans with long and short cowls are explored, as are propfans of various bypass ratios. The performance and noise comparisons of the engines are made using consistent technology standards; this approach is not apparently available in the literature. It is shown that relative to present day engines, useful improvements in Direct Operating Cost (DOC), fuel burn and noise are possible. It is shown, not surprisingly, that the optimum installed engine cycles for performance and noise are different. 2. The performance effects of using hydrogen fuel in “conventional” aero gas turbine engines are discussed. Also, some novel un-conventional hydrogen fuelled aero gas turbine cycles are examined. Hydrogen fuelled engines create no emissions of CO2; however, this environmental benefit is partly offset by the increased water in the engine contrails. It is shown that “conventional” engines benefit from using hydrogen fuel, measured by the thrust obtained for a given fuel energy input rate. The novel un-conventional configurations that are examined offer useful performance benefits, including significant power increases, by suitable use of the cold “sink” and high pressure of the liquid hydrogen fuel. 3. Two ways of eliminating CO2 emissions from industrial gas turbines are examined. The first is by use of hydrogen-rich fuel. There are performance gains, as with the aero engines; however in the industrial cases, the hydrogen is sometimes produced in such a way that it is mixed with substantial amounts of nitrogen, which significantly influences the results. The second is the use of CO2 in the working fluid for partially-closed and closed cycle arrangements. This permits easy sequestration of excess CO2 without the use of the large separating equipment that is necessary for extracting CO2 from the exhausts of standard open cycle plants breathing air. The changes required to a standard gas turbine to allow it to use CO2 as its working fluid are explored in some detail; this is not clearly addressed in the literature. It is shown that the turbines - the most expensive part of the gas turbine - can be operated satisfactorily but changes are sometimes required to the compressors.